THE SPECIFIC FEATURES OF BILINGUAL TRAINING FOR A FUTURE HISTORIAN AS A PROFESSIONAL LINGUISTIC IDENTITY - Zhanna Uriyevna Malookaya (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with formation of constructive relations in the bilingual education system for future historians. There have been presented innovative teaching methods for developing professionally oriented foreign language competence.